It's complicated (but it doesn't have to be) : a modern guide to finding and keeping love - Brunson, Paul Carrick (Gotham Books, 2012)
A professional matchmaker and certified life coach outlines a straightforward, optimistic guide to finding romance, discussing how to assess one's marriage suitability, relationship etiquette in modern times, and the appropriate use of current technology.